Factors that Influence Women’s Decision on the Mode of Birth After a Previous Caesarean Section: A Meta-ethnography - Emma Hamilton; Karen McLaughlin; Lyndall Mollart (International Journal of Community Based Nursing and Midwifery, 2023)
Background: Caesarean section (CS) rates are continuing to rise worldwide. Elective repeat CS(ERCS) greatly contribute to the rising rate which increases unnecessary risks of maternal and neonatalmorbidity and mortality. Vaginal birth after caesarean (VBAC) is a safe mode of birth for most women;however, uptake remains low. Our objective is to find the factors that influence women’s decisionmakingto support informed choices for the mode of next birth after caesarean section (NBAC).Methods: A literature search was conducted in CINAHL, Maternity and Infant Care, Embase, EmCare,Cochrane Library and Medline databases. Primary, qualitative, peer reviewed, English languageresearch articles were assessed according to inclusion/exclusion criteria. Articles were systematicallyassessed for inclusion or exclusion. Included studies were assessed using the Critical Appraisal SkillsProgramme qualitative studies checklist, Noblit and Hare’s seven-step meta-ethnography approachsynthesised themes.Results: Fourteen primary research articles were included. Six studies on 287 women focused onVBAC, and eight studies examined both VBAC and ERCS with 1861 women and 311 blogs. Thematicanalysis yielded four primary themes: Influence of health professionals, impact of previous birthexperience, optimal experience, and being in control.Conclusion: This meta-ethnography highlights health professionals’ influence on women’s decisionmaking. To assist in decision-making, women need supportive health professionals who providethe current evidence-informed information about risks and benefits of each mode of birth. Healthprofessionals need skills to provide supportive shared decision-making, debrief women regardingindications for their primary caesarean, and address issues of safety, fear, and expectations of childbirth.